KEMAMPUAN PENGGUNAAN KATA BANTU BILANGAN WADAH BAHASA MANDARIN PADA SISWA SMA 1 KALAM KUDUS MEDAN - Andriani, Finna (Universitas Muhammadiyah Tapanuli Selatan, 2023)
AbstractThe aim of this research is to describe the level of application ability and understanding of students at SMA 1 Kalam Kudus Medan regarding the use of Mandarin auxiliary words for container numbers. To achieve this goal, researchers used a quantitative descriptive research design with random sampling techniques with 113 students of SMA 1 Kalam Kudus as the population in this study. The total sample in this study was 46 people. The instrument and data collection technique used was to give test questions in the form of 15 complete questions to students at SMA 1 Kalam Kudus Medan to measure their ability to use Mandarin auxiliary words for container numbers. The instrument reliability coefficient obtained in this study using the KR-20 formula is 1, which means the instrument used in this study has a very high reliability coefficient. The average value of students in using the container number auxiliary word